An unexpected species complex unveiled in southern European populations of Phragmatiphila nexa (Hübner, [1808]) (Lepidoptera, Noctuidae, Noctuinae, Apameini) - Govi, Guido; Fiumi, Gabriele; Barbut, Jerome; Scalercio, Stefano; Hausmann, Axel (Zootaxa, 2022)
DNA barcoding analyses of Phragmatiphila nexa (Hübner, 1808) populations unveiled an unexpected divergence in mtDNA of Italian populations, showing the existence of three allopatric cryptic species. The northernmost BIN is shared with specimens from most other European countries, the southernmost one includes specimens from Basilicata and Calabria regions, and the last BIN includes specimens from Apennines, Sardinia and Corsica. Wing pattern as well as male and female genitalia support the existence of three different species along the Italian peninsula: Phragmatiphila nexa north of the Po River for which we designate a neotype, Phragmatiphila insularis (Turati, 1913), stat. rev. in the Apennines as well as in Sardinia (and Corsica), and Phragmatiphila parenzani sp. n. in the south. The Italian distribution of the genus Phragmatiphila is presented in detail.